Politik Hukum Pengujian Peraturan Perundang-Undangan dalam Penyelenggaraan Negara - Triningsih, Anna (Mahkamah Konstitusi Republik Indonesia, 2016)
Legislation or commonly called the law is a political product. Politics is a field in the society which relate to public goals, and the law as one of the fields in society is always linked to the goals of society. Because of being associated with these objectives, the law has its own dynamics side. In its socio-political dynamics there is always a message that wants to be heard, known, understood, and then executed by the addressee, which is the organizer of state power, political power holders. In the perspective of constitutional law that message then becomes a goal in organizing the state and then organized into a political structure as the procedures in the administration of the state in order to reach the goal of the state. The meaning of a more democratic state administration and based on law as a goal in the amendment of the 1945 Constitution was to provide a constitutional basis, (i) equal relationship between state and society based on rights and obligations in reciprocal nature; (ii) the equal relationship between state institutions based on checks and balances system; (iii) strengthening the independence and impartiality of judicial authority to guard the running of the legal and constitutional system. Review of egal products in state administration through judicial mechanism aims to provide a guarantee for the implementation of these relationships and the running of the legal and constitutional system in accordance with the 1945 Constitution.